2020
DOI: 10.3390/ijms21072651
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Taste Receptor mTAS1R3 in Chemical Communication of Gametes

Abstract: Fertilization is a multiple step process leading to the fusion of female and male gametes and the formation of a zygote. Besides direct gamete membrane interaction via binding receptors localized on both oocyte and sperm surface, fertilization also involves gamete communication via chemical molecules triggering various signaling pathways. This work focuses on a mouse taste receptor, mTAS1R3, encoded by the Tas1r3 gene, as a potential receptor mediating chemical communication between gametes using the C57BL/6J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The observed T1R3 expression pattern was consistent with the results of our previous study of mice [11]. The expression pattern of T1R3 and its related taste signaling components in germ cells and their potential functions have mainly been reported in mice [6,9,10,12,27,28]. The components of sweet/umami taste-related signaling cascades, such as T1R1, T1R2, T1R3, G αgust , G γ13gust , PLCβ2, and TRMP5, have been detected in spermatogenic cells of mice, in some cases, these molecules have been observed in the testicular basal layer, Leydig cells and epididymal spermatozoa [7,8].…”
Section: Discussionsupporting
confidence: 90%
“…The observed T1R3 expression pattern was consistent with the results of our previous study of mice [11]. The expression pattern of T1R3 and its related taste signaling components in germ cells and their potential functions have mainly been reported in mice [6,9,10,12,27,28]. The components of sweet/umami taste-related signaling cascades, such as T1R1, T1R2, T1R3, G αgust , G γ13gust , PLCβ2, and TRMP5, have been detected in spermatogenic cells of mice, in some cases, these molecules have been observed in the testicular basal layer, Leydig cells and epididymal spermatozoa [7,8].…”
Section: Discussionsupporting
confidence: 90%
“…Besides, T2Rs has ectopic expression during spermatogenesis in human ( Governini et al, 2020 ). Besides, T1r1 and T1r3 are present in the spermatozoa during the immotile to motile phases when spermatozoa are transported to the epididymis for maturation and storage ( Frolikova et al, 2020 ). Moreover, T2Rs are expressed in cumulus and granulosa cells, essential for oocyte development and fertilization ( Semplici et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The acrosome response of spermatozoa occurs in the female reproductive tract, where l -glutamate is present as a physiological ligand for T1r3. In vitro chemotaxis experiments showed that acrosome responsive spermatozoa are significantly attracted to l -glutamate, which provides a new perspective to resolve the complex fertilization process ( Frolikova et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sperm may have chemosensory receptors which likely get activated on encountering their cognate ligands. In mammalian species, olfactory receptors (Flegel et al, 2016) and taste receptors (Frolikova et al, 2020) have been of interest as molecular sensors for sperm-egg communication; however, their physiologically relevant ligands have not been identified yet. In general, receptor-ligand interaction in the ampulla of the oviduct leads to rapid downstream signal transduction resulting in sperm flagellar motor activation and regulation of motility to modulate its swimming path (Inaba, 2003).…”
Section: Introductionmentioning
confidence: 99%